Implementasi Peraturan Pemerintah Nomor 24 Tahun 2016 terhadap Daerah Kerja Pejabat Pembuat Akta Tanah - Anak Agung Sagung Saviti Mahawishwa Karmani; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Jurnal Preferensi Hukum, 2022)
The arrangement of the PPAT work area is formulated in PP No. 24 of 2016 Article 12 Paragraph 1 formulates that the PPAT working area includes the province where the PPAT office is located. This research discusses the implementation of the PPAT work area and the sanctions that will be obtained if the PPAT exercises authority outside its working area. This research aims to discuss the legal arrangements regarding the work area of ​​the Land Deed Making Official and to find out the sanctions against the Land Deed Maker Officer who exercises authority outside the work area. This research is normative research using a statutory approach and a conceptual approach. The sources of legal materials for this research consist of primary, secondary, and tertiary sources of material. The collection of primary and secondary legal materials is carried out by collecting, reading, and recording legal materials in accordance with the laws related to the issues in this research. The results of this research explain that PP no. 24 of 2016 in Article 12 Paragraph 1 is not implemented according to the contents of the regulation. There is no article that explains the sanctions if the PPAT does not carry out the work area of ​​one province so that the PPAT who exercises authority outside the work area does not get sanctions. This implementation contradicts the Lex Posterior Derogat Legi Priori Principle.